ANALISIS TINGKAT PENDAPATAN PEDAGANG KAKI LIMA DI JALAN AHMAD YANI (TEPIAN SUNGAI SEGAH) TANJUNG REDEB - Hakim, Abdul (ECO-BUILD, 2018)
This study aims to determine whether significantly the average income level of street sellers in Jalan Ahmad Yani (Tepian Sungai Segah) Tanjung Redeb has been above the Berau Living Needs (BLN) of Berau District in 2017. The usefulness of this      research is knowing and getting the picture average income level of the Street Traders on Jalan Ahmad Yani (Tepian Sungai Segah) Tanjung Redeb. This information is expected to be useful for the local government of Berau District in taking steps in handling or management of street vendors in the area of ​​Jalan Ahmad Yani (Tepian Sungai Segah) Tanjung Redeb The results showed that based on t test results at 95% confidence level and degrees of freedom of n-1 is known t value count (th) is 9.214 while the value of t in the table is equal to 1.761. Because the value of t arithmetic greater than the value of t on the table (th> tt), thus the hypothesis proposed authors accepted, it means that the income of street vendors in Jalan Ahmad Yani (Edge River Segah) Tanjung Redeb already above the standard of Living Needs Berau District Year 2017.